Photon-pair generation for quantum computing applications - Lim, Zander Kar Wee (Nanyang Technological University, 2023)
This project aims to develop a consistent source of entangled photon pairs to be used for quantum computing applications under Asst Prof Nam Donguk’s team. This report documents the process of designing, building, and testing the set-up. Firstly, research is done to identify the best design and components for the set-up. In the case of this project, Spontaneous Parametric Down Conversion (SPDC) is the chosen means to generate the entangled photon pairs. Secondly tests are carried out on the signal photons to determine whether the photons generated have the characteristics of entanglement. The test selected are the Hong-Ou-Mandel experiment to test for indistinguishability and the Bell Test to check for entanglement. If successful, the set-up will serve as an important entangled photon source for quantum computing experiments.